Report of joint meeting of I.F.T.U. Executive and L.S.I. Bureau on Wednesday, February 17th, 1937, at 3 p.m., in Paris - International Federation of Trade Unions ; Labour and Socialist International
1937-02-17 022_0001-001 292/946/22/1(i)